CD80 Expressed by CD8+ T Cells Contributes to PD-L1-Induced Apoptosis of Activated CD8+ T Cells - Meagan R. Rollins; Rachel M. Gibbons Johnson (Journal of Immunology Research)
Tumor cells are capable of limiting antitumor CD8+ T cell responses through their cell surface expression of PD-L1. In addition to PD-1 expressed by CD8+ T cells, PD-L1 also binds to CD80 expressed by CD8+ T cells. The influence of the PD-L1/CD80 interaction on CD8+ T cell function has not been fully characterized, so we sought to investigate the impact of the PD-L1/CD80 interaction on PD-L1-induced apoptosis of activated CD8+ T cells. We found that CD8+ T cells that lacked CD80 expression got activated to the same extent as wild-type CD8+ T cells, but when cultured with anti-CD3 and PD-L1/Fc protein, activated CD8+ T cells that lacked CD80 expression survived better than activated wild-type CD8+ T cells. These findings indicate that PD-L1 induces apoptosis in activated CD8+ T cells in part by signaling through CD80. Thus, in the design and implementation of checkpoint blockade therapies that target PD-L1, it is essential that both binding partners for PD-L1, PD-1, and CD80 are considered.